Обґрунтування процесу переходу агропідприємств на органічне виробництво та заходи практичної реалізації концепції екологічного маркетингу - Багорка, Марія Олександрівна; Bahorka, Mariia; Юрченко, Наталія Іванівна; Yurchenko, Nataliy (НАУКОВО-ОСВІТНІЙ ІННОВАЦІЙНИЙ ЦЕНТР СУСПІЛЬНИХ ТРАНСФОРМАЦІЙ, 2024)
Метою статті є обґрунтування необхідності, аналіз поточного стану та розробка заходів впровадження концепції екологічного маркетингу в діяльність аграрних підприємств з метою покращення сталості, зменшення негативного впливу на довкілля та забезпечення задоволення потреб споживачів. В межах дослідження було розглянуто методичні, правові, організаційні та маркетингові підходи, які допоможуть здійснити процес переходу на органічне виробництво та концепцію екологічного маркетингу аграрного підприємства, при цьому детально розглянуто і надано пропозиції стосовно використання елементів комплексу маркетингу, доповнених відповідно до екологічно орієнтованого агровиробництва. Робоча гіпотеза: передбачається, що шляхом розробки організаційних заходів переходу аграрних підприємств на органічне виробництво та впровадження концепції екологічного маркетингу в їх діяльність буде максимізований рівень прибутковості аграрних підприємств. Основою методичних підходів при розробці рекомендацій переходу аграрних підприємств на органічне виробництва були теоретичні положення концепції сталого розвитку та екологічного маркетингу, методи економічного та стратегічного аналізу, за допомогою яких проведено діагностику та оцінку еколого-економічного потенціалу галузі; визначено потенційні можливості аграрних підприємств, пов’язані з їх переходом на екологічно орієнтоване виробництво. За допомогою порівнянь було проведено узагальнення основних складових концепції екологічного маркетингу та органічного землеробства, та встановлення зв’язку між ними. In connection with the strengthening of the negative impact of the economic activity of society on the state of the environment, including the sphere of agricultural production, and the need to provide the population with high-quality and safe food products, the ecologically oriented direction of agricultural production and the implementation of the concept of ecological marketing in the activities of agricultural enterprises are gaining relevance. The purpose of the article is to substantiate the need, analyze the current state, and develop measures to implement the concept of ecological marketing in the activities of agricultural enterprises in order to improve sustainability, reduce the negative impact on the environment, and ensure the satisfaction of consumer needs. Methodological, legal, organizational and marketing approaches that will help to implement the process of transition to organic production and the concept of ecological marketing of an agrarian enterprise were considered within the scope of the study, while suggestions were given in detail regarding the use of elements of the marketing complex supplemented in accordance with eco logically oriented agricultural production. Working hypothesis: it is assumed that the level of profitability of agricultural enterprises will be maximized through the development of organizational measures for the transition of agricultural enterprises to organic production and the introduction of the concept of ecological marketing into their activities. The basis of methodological approaches in the development of recommendations for the transition of agricultural enterprises to organic production were the theoretical provisions of the concept of sustainable development and ecological marketing, methods of economic and strategic analysis, which were used to diagnose and assess the ecological and economic potential of the industry; the potential opportunities of agricultural enterprises related to their transition to ecologically oriented production are determined. With the help of comparisons, the main components of the concept of ecological marketing and organic farming were summarized, and the connection between them was established. Reasonable needs in organic farming, its advantages and limitations.
Justification of the process of transition of agricultural enterprises to organic production and measures for the practical implementation of the ecological marketing concept
Keywords: концепція екологічного маркетингу; соncept of ecological marketing; аграрні підприємства; agricultural enterprises; органічне агровиробництво; organic agricultural production; органічна продукція; organic products; комплекс маркетингу; marketing complex; фактори мотивації; motivation factors; канали розподілу; distribution channels; інформаційні джерела; information sources